Pengembangan Booklet Digital Hipertensi Berbasis Research and Development dan Uji Keterbacaannya Pada Usia Produktif - Victoria, Arlies Zenitha; Jona, Resa Nirmala; Arwinda, Sherly (Yayasan Jompa Research and Development, 2025)
Background: Health education plays a crucial role in improving patients’ knowledge and adherence, with digital media such as digital booklets increasingly adopted for their accessibility, flexibility, and effectiveness in enhancing patient self-management. However, the effectiveness of educational media is highly dependent on its readability level. Materials with poor readability may lead to misunderstanding and reduced engagement. This study aimed to identify the readability level of a digital booklet for productive-age adults with hypertension as an initial step to ensure the effectiveness of digital health education media. Method: This study employed a quantitative descriptive design with a research and development (R&D) approach to develop a digital educational booklet using the Heyzine platform, enhanced with AI-generated voice-over. Readability testing was conducted among 21 productive-age adults with hypertension in Semarang City using the Cloze Test, Multiple Choice Questions (MCQ), and a subjective questionnaire. Expert validation was performed by two reviewers specializing in community nursing and Indonesian language using The Patient Education Materials Assessment Tool–Printable version (PEMAT-P), which evaluates the domains of understandability and actionability. Result: The readability test results showed excellent scores, with a Cloze Test score of 94.29%, MCQ score of 92%, and a subjective questionnaire mean score of 4.22 out of 5. The expert validation using PEMAT-P indicated an understandability score of 79.41% and an actionability score of 78.57%, suggesting that the digital booklet is suitable for use as an educational tool for hypertension management. Conclusion: The readability and expert validation results demonstrated that the digital booklet possessed high levels of understandability and applicability (Cloze Test 94.29%; MCQ 92%; subjective questionnaire 4.22; PEMAT-P 78.99%), making it a feasible medium for health education among productive-age adults with hypertension. Future research is recommended to involve larger samples, more expert reviewers, and additional readability assessment instruments.